BURNING MOUTH SYNDROME: PATHOPHYSIOLOGY, CLINICAL CHARACTERISTICS, AND MANAGEMENT - Susanna Halim; Erni Haryanti; Mhd. Deriansya (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Burning Mouth Syndrome (BMS) is a chronic orofacial pain condition characterized by burning, tingling, or dysesthetic sensations in the oral mucosa without clinically visible mucosal lesions or identifiable local causes. It remains a diagnostic challenge in dental practice because its clinical manifestations are associated with neuropathic, psychoneurological, salivary, systemic, and psychological factors. This literature review aimed to describe the pathophysiology, clinical characteristics, diagnosis, and management of BMS, with particular emphasis on neuropathic mechanisms, psychoneurological aspects, salivary alterations, and their impact on quality of life. A narrative literature review with a thematic approach was conducted using 25 selected articles, including case reports, case-control studies, randomized clinical trials, observational studies, cohort/follow-up studies, scoping reviews, and systematic reviews published between 2021 and 2025. The findings indicate that BMS is a multifactorial condition involving small fiber neuropathy, trigeminal nociceptive dysfunction, central dopaminergic alterations, salivary and oral microbiome changes, psychological factors, sleep disturbances, systemic comorbidities, and drug-related mechanisms. Diagnosis is primarily clinical and exclusion-based, requiring evaluation of the oral mucosa, salivary complaints, taste disturbances, nutritional status, systemic conditions, medication history, and psychological factors. Management strategies include patient education, correction of secondary causes, topical or systemic pharmacotherapy, photobiomodulation, low-level laser therapy, oral cryotherapy, psychological support, and individualized multidisciplinary care. BMS requires a comprehensive diagnostic approach and individualized management to prevent unnecessary dental treatment and improve clinical outcomes and quality of life. ABSTRAK Burning Mouth Syndrome (BMS) merupakan kondisi nyeri orofasial kronis yang ditandai dengan sensasi terbakar, kesemutan, atau disestesia pada mukosa oral tanpa adanya lesi mukosa yang tampak secara klinis maupun penyebab lokal yang jelas. Kondisi ini masih menjadi tantangan diagnostik dalam praktik kedokteran gigi karena manifestasinya berkaitan dengan berbagai faktor neuropatik, psikoneurologis, saliva, sistemik, dan psikologis. Kajian ini bertujuan mendeskripsikan patofisiologi, karakteristik klinis, diagnosis, dan tatalaksana BMS dengan penekanan pada mekanisme neuropatik, aspek psikoneurologis, perubahan saliva, serta dampaknya terhadap kualitas hidup. Penelitian ini menggunakan narrative literature review dengan pendekatan tematik terhadap 25 artikel yang terdiri atas case report, case-control study, randomized clinical trial, observational study, cohort/follow-up study, scoping review, dan systematic review yang diterbitkan pada 2021–2025. Hasil kajian menunjukkan bahwa BMS merupakan kondisi multifaktorial yang melibatkan small fiber neuropathy, disfungsi nosiseptif trigeminal, perubahan dopaminergik sentral, perubahan saliva dan mikrobioma oral, faktor psikologis, gangguan tidur, komorbiditas sistemik, serta mekanisme terkait penggunaan obat. Diagnosis bersifat klinis dan berbasis eksklusi melalui evaluasi kondisi mukosa oral, keluhan saliva, gangguan pengecapan, status nutrisi, kondisi sistemik, riwayat penggunaan obat, dan faktor psikologis. Tata laksana meliputi edukasi pasien, koreksi faktor sekunder, terapi farmakologis topikal atau sistemik, fotobiomodulasi, terapi laser intensitas rendah, krioterapi oral, dukungan psikologis, serta perawatan multidisiplin yang disesuaikan dengan kondisi pasien. BMS memerlukan pendekatan diagnostik komprehensif dan tatalaksana individual untuk mencegah perawatan dental yang tidak diperlukan serta meningkatkan luaran klinis dan kualitas hidup pasien.